Analysis of the influence of ChatGPT on secondary education from the perspective of teachers - Miriam López Santos; Alba Lozano; Carolina Blanco Fontao (Journal of Technology and Science Education)
In the current landscape, the rapid evolution of educational technology, particularly AI tools like ChatGPT, necessitates understanding how educators perceive their integration into the education system. This study uses a quantitative, non-experimental, descriptive-comparative, and cross-sectional study was conducted with 379 active teachers in Castilla y León, Spain. The research instrument, a validated questionnaire, sought to assess prior knowledge, usage, and perceptions of ChatGPT's application in educational settings. Findings reveal high awareness and exploratory use of ChatGPT among teachers, though practical implementation and specific training remain limited. Teachers acknowledge ChatGPT's potential to enhance educational processes, particularly in generating educational materials and planning tasks. However, significant concerns about plagiarism, critical thinking, and ethical use persist. Differences in perceptions are mainly influenced by specialty, age, and gender, highlighting the need for tailored training and policies to support effective and ethical AI integration in education. These insights underscore the importance of continuous professional development to harness AI's benefits while mitigating associated risks.